2016
DOI: 10.1016/j.bbabio.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The two Dps proteins, NpDps2 and NpDps5, are involved in light-induced oxidative stress tolerance in the N2-fixing cyanobacterium Nostoc punctiforme

Abstract: Cyanobacteria are photosynthetic prokaryotes that are considered biotechnologically prominent organisms for production of high-value compounds. Cyanobacteria are subject to high-light intensities, which is a challenge that needs to be addressed in design of efficient bio-engineered photosynthetic organisms. Dps proteins are members of the ferritin superfamily and are omnipresent in prokaryotes. They play a major role in oxidative stress protection and iron homeostasis. The filamentous, heterocyst-forming Nosto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 63 publications
1
24
0
Order By: Relevance
“…However, the strongest induction was observed for the dps gene (~28-fold), which codes for the “ D NA-binding p rotein from s tarved cells” (Dps) that is known to protect DNA against ROS-mediated damage in E . coli and other bacteria 80 83 . Furthermore, most of the suf genes are induced via DsFbFP M49I-dependent ROS formation.…”
Section: Resultsmentioning
confidence: 99%
“…However, the strongest induction was observed for the dps gene (~28-fold), which codes for the “ D NA-binding p rotein from s tarved cells” (Dps) that is known to protect DNA against ROS-mediated damage in E . coli and other bacteria 80 83 . Furthermore, most of the suf genes are induced via DsFbFP M49I-dependent ROS formation.…”
Section: Resultsmentioning
confidence: 99%
“…BFR from Pseudomonas aeruginosa needs the presence of the ferrodoxin encoded by the neighboring gene Bfd for a fast reductive iron release in vitro . The N 2 ‐fixing cyanobacterium Nostoc puntiforme has 5 Dps and only two of them are important for fitness under high illumination and differentiation photosystem . The function of the encapsulin EncFtn as iron storage molecule so far has been observed only in vivo.…”
Section: Ferritin and Iron Storage In Bacteriamentioning
confidence: 99%
“…However, the specific functions of the individual Dps and cooperative behavior of multiple Dps proteins within one organism for cellular fitness, including iron homeostasis and oxidative stress tolerance, have not been resolved. As previously mentioned, the working hypothesis of our earlier studies was that multiple Dps proteins within one organism have different and specific function of importance for cell homeostasis (8,21), and that these differences would be reflected in the biochemical properties of the individual Dps. The results obtained in the present in vitro and in silico studies indeed show clear differences in the individual biochemical properties of the three canonical Dps proteins NpDps1, NpDps2, and NpDps3, as summarized in Table 2.…”
Section: Discussionmentioning
confidence: 90%
“…This might seem contradictory to our earlier functional genetics studies in which only one of the three, NpDps2, was shown to have a crucial physiological role in the presence of high exogenously added H 2 O 2 levels (8). However, although the physiological relevance of the iron uptake and iron oxidation by H 2 O 2 is hard to predict, the in vivo roles could to some extent be understood by the determined differential gene and protein expression of NpDps (8,9,21,45,46). The NpDps-specific expression is distributed among the various cell types, formed during specific cultivation conditions, of N. punctiforme (12), which suggests growth condition-specific functions of the three canonical NpDps proteins.…”
Section: Iron Attraction and Entry Into The Npdpsmentioning
confidence: 99%